NEW VOCABULARY LEARNING STRATEGIES USED BY FIRST YEAR STUDENTS OF FACULTY OF ENGLISH LANGUAGE TEACHER EDUCATION,UNIVERSITY OF LANGUAGES AND INTERNATIONAL STUDIES, VIETNAM NATIONAL UNIVERSITY - Phạm, Thị Thư (2020)
The present investigation aims to investigate threefold: 1) to examine the perceptions of first year students of Faculty of English language and teacher education – ULIS - VNU of English vocabulary and vocabulary learning strategies; 2) to explore the frequency of students’ reported strategy use of three main vocabulary categories: the discovery of the meaning of new vocabulary items (DMV), the retention of the knowledge of newly- learned vocabulary items (RKV), and the expansion of the knowledge of vocabulary (EKV) and 3) to search for effective vocabulary learning strategies suggested by experts. The research subjects of the study were 100 first year students of FELTE – ULIS – VNU in academic year 2010 - 2011, obtained through the multi-stage sampling. Interviews and a strategy questionnaire were used as the main methods for data collection. Through the interviews, all students acknowledged the significance of a rich personal vocabulary to English learning. The majority of them are willing to study vocabulary learning strategies formally in class. The statistical methods used in order to help interpret the data for the survey questionnaire are mean of frequency ( ) and standard deviation (S.D.). First year students, on a whole, reported medium frequency of strategy use for their vocabulary learning.